2016
DOI: 10.1161/jaha.116.003731
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospital Performance on Patient Safety and 30‐Day Mortality and Unplanned Readmission for Medicare Fee‐for‐Service Patients With Acute Myocardial Infarction

Abstract: BackgroundLittle is known regarding the relationship between hospital performance on adverse event rates and hospital performance on 30‐day mortality and unplanned readmission rates for Medicare fee‐for‐service patients hospitalized for acute myocardial infarction (AMI).Methods and ResultsUsing 2009–2013 medical record‐abstracted patient safety data from the Agency for Healthcare Research and Quality's Medicare Patient Safety Monitoring System and hospital mortality and readmission data from the Centers for Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
0
17
2
Order By: Relevance
“…As noted in the Discussion, our study focused on the association of AMI outcomes and scores from the commonly used, generic AHRQ safety culture survey instrument. More AMI-focused survey instruments (Bradley et al 2012(Bradley et al , 2014 and other proxy indicators of safety culture such as adverse event rates (Wang et al 2016) have demonstrated associations not found in our study.…”
Section: Limitationscontrasting
confidence: 88%
“…As noted in the Discussion, our study focused on the association of AMI outcomes and scores from the commonly used, generic AHRQ safety culture survey instrument. More AMI-focused survey instruments (Bradley et al 2012(Bradley et al , 2014 and other proxy indicators of safety culture such as adverse event rates (Wang et al 2016) have demonstrated associations not found in our study.…”
Section: Limitationscontrasting
confidence: 88%
“…This is particularly important in the post‐CABG population, where many patients may benefit from earlier and closer medical surveillance (especially in the setting of the global surgical fee). Furthermore, institutions with poorer patient safety performance have been associated with greater unplanned readmissions 22. Additional follow‐up measures, including provider‐initiated telephone or videophone communication, the use of remote telemonitoring, provider home visits, and patient‐directed rehabilitation efforts, should be considered and intensified 19…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of an inverse association between marijuana use and in‐hospital mortality deserves further study. It is possible that advancements in medical care, including rapid diagnosis and high‐quality treatment that has led to a substantial improvement in hospitalization outcomes for cardiovascular disease and reduction in adverse events regardless of underlying risk factors or exposure such as marijuana use. It is also possible that among older, sicker adults, marijuana use not accompanied by other illicit or harmful risk factors such as cocaine and/or alcohol use , but is associated with some health benefits such as reduced risk of adverse cardiac outcomes.…”
Section: Discussionmentioning
confidence: 99%